Morgen, een festival voor de toekomst : Stichtingfestival Arnhem 1980. - Hofman, Herman; Spiekerman, Marjolein (Arnhem : Stichting Festival, 1981)
Courbois, Pierre ; Mengelberg, Misha ; Raaijmakers, Dick ; Kolvenbach, Floris ; Van Bergeijk, Gilius ; Klaver, Moniek Toebosch / Kees ; Stokvis, CCC ; DDV/Viadukt ; Schouwburg, Manifestatie ; Alberts, Armeno ; Jaa, Trio ; Van Zijp, Hans ; Beenen, Dansakademie Anneloise ; Arts, Arno ; Gieling, Ramon ; Kooi), Ma Prem Els (Els Van der ; Smits, Maayke De Ridder / Lilian ; Joseph, Pier Van Dijk / Robert ; Krooshof, Bert ; de Ridder, Willem ; Starrats ; Gregoor, Wim ; Payens, Boudewijn ; Aalders, Franklin ; Companjen, Irene ; Gerritsen, Juul ; Robaard, Joke ; Klumperink, Robaard / VD Laaken / ; van der Laaken, Ton ; Klumperink, Ben ; Korvinus, Willem ; Vroegindeweij, Leo ; King, Tjoe Fang ; Theuws, Roos ; Vleeshouwer, Co ; van Summeren, Ton ; Mark, Aarnoud Van Der ; Jansen, Servie ; Mommersteeg, Leon ; Tomassen, Theo ; Milder, Huub ; Bakker, Brandje ; Wittenrood, Pauline ; Eijkelboom, Hans ; Van Ommen, Catherien ; Gerritsen, Ad ; Hendriks, Marten ; Van Kleef, Diederick ; Vorming, Bureau Kunstzinnige
festivalverslag, Arnhem, 28.06. - 06.07.1980
Nederlands
boek